Aerosols Science and Case Studies - Volkov, Konstantin (IntechOpen, 2016)
Aerosols have a significant impact on technological processes and human activities. In many cases, aerosols are at the core of human health, environmental and technological problems (climate change and air quality). However, aerosols can be successfully used in industry and technology (new materials, fire suppression and fuel delivery). The current scientific status of aerosol modelling and simulation and measurements and some advances in computational techniques, particle measurement technologies and practical applications of aerosols are reviewed and considered in this book. This book also includes a number of case studies focused on analysis of optical thickness and air quality in various regions.